Problematic Internet Use dalam Perspektif Psikologi: Kajian Literatur - Rahmi, Harsa Afifatur; Chairani, Lisya (Universitas Al Azhar Indonesia, 2025)
Internet use has become an essential part of modern life. However, when used excessively and without control, it may develop into Problematic Internet Use (PIU). PIU is characterized by maladaptive behaviors that disrupt individuals’ psychosocial functioning, academic performance, and daily life. This article aims to provide a comprehensive review of the literature on PIU, including its definitions, conceptual development, psychological aspects, and contributing factors. Findings show that PIU is not merely about screen time but involves a preference for online interaction, emotional regulation, and poor self-control. Personal factors such as low self-esteem and psychological distress, along with social influences and early life experiences, contribute to the risk of developing PIU. A deeper understanding of PIU is expected to serve as a foundation for preventive and intervention efforts to help individuals, especially adolescents and young adults, use the internet in a healthy and adaptive manner. This study can provide a comprehensive conceptual understanding of Problematic Internet Use (PIU). In addition, it can serve as a foundational reference for anyone who wishes to conduct further research or gain a deeper understanding of PIU.Keywords - Mental Health, Online Behavior, Problematic Internet Use.